Searching for the best medicine : the life and times of a doctor and patient - Bank, Arthur (World Scientific, 2013)
This book describes the life and times of a physician-scientist over the last half-century. Part One is about the author's struggle with colon cancer and the lessons he learnt from the experience; Part Two is about his life growing up, the pretzel bakery, his family, being educated at Bronx Science, Columbia College, Harvard Medical School, and his medical training at the Boston City Hospital and the NIH. Part Three, the major portion of the book, describes the author's experiences as a practicing physician and hematologist at Columbia-Presbyterian Medical Center over 40 years. It also present.